Role of endothelium-derived relaxing factor in renal autoregulation in conscious dogs - Baumann, J. Ê.; Persson, Pontus B.; Ehmke, Heimo; Nafz, Benno; Kirchheim, Hartmut (American journal of physiology. Renal physiology, 1992)
In six chronically instrumented, conscious dogs the hypothesis was tested that the release of endothelium-derived relaxing factor (EDRF) is important for autoregulation of renal blood flow (RBF) and glomerular filtration rate (GFR). RBF was measured by a Transonic flowmeter. Renal perfusion pressure was servo-controlled by an aortic cuff. EDRF synthesis was inhibited by NG-nitro-L-arginine methyl ester (L-NAME, 50 mg/kg iv). L-NAME increased mean systemic blood pressure (30 mmHg) and decreased heart rate (-40 beats/min), but it left autoregulation of RBF and GFR intact. However, basal RBF decreased markedly (2.24 +/- 0.32 ml.min-1.g-1 with L-NAME vs. 3.91 +/- 0.64 ml.min-1.g-1 for control, P less than 0.01), whereas basal GFR was not significantly influenced (0.37 +/- 0.05 ml.min-1.g-1 with L-NAME vs. 0.42 +/- 0.06 ml.min-1.g-1 for control). Hence filtration fraction increased with L-NAME [27.6 +/- 1.7% vs. 19.3 +/- 1.3% (P less than 0.01)]. The lower limit of autoregulation remained unchanged for RBF (64 +/- 5 mmHg with L-NAME vs. 63 +/- 3 mmHg for control) and increased slightly for GFR (74 +/- 2 mmHg with L-NAME vs. 67 +/- 1 mmHg for control, P less than 0.01). In conclusion, basal EDRF activity tonically influences renal resistance vessels; however, EDRF release is not primarily involved in the process of renal autoregulation. The maintenance of GFR suggests that this effect is localized in preglomerular as well as in postglomerular arterioles.
Gesehen am 02.12.2024